Copolymers, molded bodies, injection molded bodies and coated electric wires

CN116897170BActive Publication Date: 2026-10-09DAIKIN INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280016005.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-01-31
Publication Date
2026-10-09
Estimated Expiration
2042-01-31

AI Technical Summary

Benefits of technology

[0014] According to the present invention, a copolymer can be provided that can be obtained with high productivity by injection molding to produce injection molded articles with excellent surface smoothness, can be easily formed with a thin coating layer of uniform thickness and few defects on a core wire with a small diameter by extrusion molding, and can produce molded articles with excellent haze value, abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics, and heat deformation resistance after reagent impregnation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004403953840000051
    Figure BDA0004403953840000051
  • Figure BDA0004403953840000171
    Figure BDA0004403953840000171
  • Figure BDA0004403953840000191
    Figure BDA0004403953840000191
Patent Text Reader

Abstract

The present application provides a copolymer containing tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, the content of the perfluoro(propyl vinyl ether) units being 2.14 mol% to 3.00 mol% relative to the total monomer units, the melt flow rate at 372°C being 33.0 g / 10 minutes to 50.0 g / 10 minutes, the number of functional groups being 50 or less per 10 6 main chain carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to copolymers, molded articles, injection molded articles, and coated wires. Background Technology

[0002] Patent Document 1 describes a USB cable for transmitting data at ultra-high speeds of at least 10 GHz. The USB cable includes a sheath containing at least a power cable for transmitting data at a maximum speed of 10 Gbps per channel and a plurality of shielded insulated conductors. The insulator in the insulated conductors exhibits a dielectric loss tangent of less than 0.00035 at 10 GHz and comprises a melt-processable perfluoropolymer. The melt-processable perfluoropolymer is composed of a tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymer or a tetrafluoroethylene (TFE) / perfluoro(alkyl vinyl ether) (PAVE) copolymer, wherein the alkyl group contains 1 to 5 carbon atoms.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Publication No. 2018-523272 Summary of the Invention

[0006] The problem that the invention aims to solve

[0007] The purpose of this invention is to provide a copolymer that can produce injection molded articles with excellent surface smoothness at high productivity through injection molding, can easily form a thin coating layer with uniform thickness and few defects on a core wire with a small diameter through extrusion molding, and can produce molded articles with excellent haze value, abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics, and heat deformation resistance after reagent impregnation.

[0008] Methods for solving problems

[0009] According to the present invention, a copolymer is provided comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, wherein the content of perfluoro(propyl vinyl ether) units is 2.14 mol% to 3.00 mol% relative to all monomer units, the melt flow rate at 372°C is 33.0 g / 10 min to 50.0 g / 10 min, and the number of functional groups is relative to the number of monomer units per 10 ... 6 The number of carbon atoms in the main chain is less than 50.

[0010] In addition, according to the present invention, an injection-molded article is provided which contains the above-mentioned copolymer.

[0011] In addition, according to the present invention, a coated wire is provided having a coating layer containing the above-mentioned copolymer.

[0012] In addition, according to the present invention, a molded body is provided, which is a molded body containing the above-mentioned copolymer, wherein the molded body is a connector, a flow meter body or a wire cover.

[0013] The effects of the invention

[0014] According to the present invention, a copolymer can be provided that can be obtained with high productivity by injection molding to produce injection molded articles with excellent surface smoothness, can be easily formed with a thin coating layer of uniform thickness and few defects on a core wire with a small diameter by extrusion molding, and can produce molded articles with excellent haze value, abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high temperature rigidity, high temperature tensile creep characteristics, and heat deformation resistance after reagent impregnation. Detailed Implementation

[0015] The specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments.

[0016] The copolymer of the present invention contains tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units.

[0017] Patent Document 1 describes the use of melt-processable perfluoropolymer to form the sheath of a USB cable. However, if the melt-processable perfluoropolymer described in Patent Document 1 is used to form molded bodies such as flow meter components for measuring the flow rate of reagents and piping components for conveying reagents, the resulting molded bodies have insufficient transparency, high-temperature wear resistance, and heat deformation resistance after reagent impregnation, and there is room for improvement.

[0018] By appropriately adjusting the PPVE unit content, melt flow rate (MFR), and number of functional groups in copolymers containing TFE and PPVE units, it is possible to easily form thin coatings with uniform thickness and few defects on core wires with small diameters. Furthermore, by using such copolymers, injection-molded parts with excellent surface smoothness can be obtained with high productivity.

[0019] Furthermore, it was found that copolymers with appropriately adjusted PPVE unit content, melt flow rate (MFR), and functional group number can provide molded articles with low haze values, excellent abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics, and excellent heat resistance after reagent impregnation. Therefore, by using such copolymers as materials for molded articles, such as those used to form flow meter components for measuring reagent flow rates and piping components for conveying reagents, flow meters capable of reliably measuring flow rates and piping components capable of confirming reagent delivery status can be obtained. Moreover, these molded articles exhibit excellent abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics, and heat resistance after reagent impregnation, thus minimizing deformation even when in contact with high-temperature reagents and preventing the permeation of reagents such as oxygen, electrolytes, and organic solvents, thereby minimizing changes in reagent quality.

[0020] The copolymers of the present invention are melt-processable fluoropolymers. Melt processability refers to the ability to melt and process the polymer using existing processing equipment such as extruders and injection molding machines.

[0021] The content of PPVE units in the copolymer relative to all monomer units is 2.14 mol% to 3.00 mol%, preferably 2.17 mol% or more, more preferably 2.20 mol% or more, even more preferably 2.23 mol% or more, particularly preferably 2.26 mol% or more, most preferably 2.30 mol% or more, preferably 2.90 mol% or less, more preferably 2.85 mol% or less, even more preferably 2.80 mol% or less, and particularly preferably 2.75 mol% or less. By keeping the content of PPVE units in the copolymer within the above range, a molded article with low haze value, excellent abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics, and excellent heat deformation resistance after reagent impregnation can be obtained. If the content of PPVE units in the copolymer is too low, the haze value of the obtained molded article will be high, and the abrasion resistance at 150°C and the heat deformation resistance after reagent impregnation will be poor.

[0022] The content of TFE units in the copolymer relative to all monomer units is preferably 97.00 mol% to 97.86 mol%, more preferably 97.10 mol% or more, even more preferably 97.15 mol% or more, particularly preferably 97.20 mol% or more, most preferably 97.25 mol% or more, more preferably 97.83 mol% or less, even more preferably 97.80 mol% or less, even more preferably 97.77 mol% or less, particularly preferably 97.74 mol% or less, and most preferably 97.70 mol% or less. By keeping the content of TFE units in the copolymer within the above range, it is possible to obtain a molded article with lower haze value, better abrasion resistance at 150°C, lower oxygen permeability, lower reagent permeability, higher temperature rigidity, higher temperature tensile creep characteristics, and better heat deformation resistance after reagent impregnation. If the content of TFE units in the copolymer is too high, the haze value of the obtained molded article will increase, and the abrasion resistance at 150°C and the heat deformation resistance after reagent impregnation may deteriorate.

[0023] In this invention, the content of each monomer unit in the copolymer is determined by... 19 Determined by F-NMR method.

[0024] The copolymer may also contain monomer units from monomers capable of copolymerizing with TFE and PPVE. In this case, the content of monomer units capable of copolymerizing with TFE and PPVE is preferably 0 to 0.86 mol% relative to all monomer units of the copolymer, more preferably 0.01 mol% to 0.30 mol%, and even more preferably 0.05 to 0.20 mol%.

[0025] Monomers capable of copolymerizing with TFE and PPVE include hexafluoropropylene (HFP) and CZ. 1 Z 2 =CZ 3 (CF2) n Z 4 (where Z) 1 Z 2 and Z 3 Same or different, represented by H or F, Z 4 Vinyl monomers (represented by H, F, or Cl, where n represents an integer from 2 to 10), CF2 = CF-ORf 1 (where Rf) 1 Perfluoro(alkyl vinyl ether) [PAVE] (except for PPVE) represented by perfluoroalkyl groups having 1 to 8 carbon atoms, and CF2=CF-OCH2-Rf 1 (where Rf is in the formula) 1 This refers to perfluoroalkyl groups having 1 to 5 carbon atoms. Alkyl perfluorovinyl ether derivatives, etc., are also included. HFP is preferred.

[0026] The copolymer is preferably selected from at least one of the groups consisting of copolymers composed only of TFE units and PPVE units, and TFE / HFP / PPVE copolymers, and more preferably copolymers composed only of TFE units and PPVE units.

[0027] The melt flow rate (MFR) of the copolymer is 33.0 g / 10 min to 50.0 g / 10 min. Preferably, the MFR of the copolymer is 33.1 g / 10 min or more, more preferably 34.0 g / 10 min or more, even more preferably 34.1 g / 10 min or more, particularly preferably 35.0 g / 10 min or more, most preferably 36.0 g / 10 min or more, preferably 49.9 g / 10 min or less, more preferably 49.0 g / 10 min or less, and even more preferably 48.0 g / 10 min or less. By keeping the MFR of the copolymer within the above range, it is possible to obtain molded articles with low haze, excellent abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics, and excellent heat deformation resistance after reagent impregnation.

[0028] Furthermore, by keeping the MFR of the copolymer within the aforementioned range, using such a copolymer enables the production of injection-molded articles with excellent surface smoothness at high productivity, and allows for the easy formation of thin coatings with uniform thickness and few defects on core wires with small diameters. Additionally, by keeping the MFR of the copolymer within the aforementioned range, the number of sparks generated in the coating obtained using such a copolymer can be reduced. Furthermore, by using the copolymer of the present invention, it is possible to simultaneously manufacture multiple small injection-molded articles having thin-walled portions.

[0029] In this invention, MFR is a value obtained according to ASTM D1238 using a melt index meter in the form of the mass (g / 10 min) of polymer flowing out of a nozzle with an inner diameter of 2.1 mm and a length of 8 mm every 10 minutes at 372°C and a load of 5 kg.

[0030] MFR can be adjusted by modifying the type and amount of polymerization initiator and the type and amount of chain transfer agent used in monomer polymerization.

[0031] In this invention, every 10 of the copolymer 6 The number of functional groups per carbon atom in the main chain is less than 50. Each 10 of the copolymer... 6The number of functional groups per carbon atom in the main chain is preferably 40 or less, more preferably 30 or less, even more preferably 20 or less, even more preferably 15 or less, particularly preferably 10 or less, and most preferably less than 6. By keeping the number of functional groups in the copolymer within the above range, a molded article with excellent abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics, and heat deformation resistance after reagent impregnation can be obtained. Furthermore, by keeping the number of functional groups in the copolymer within the above range, a thin coating layer can be formed at high speed on a core wire with a small diameter using extrusion molding. If the number of functional groups in the copolymer is too high, it is difficult to obtain a molded article with excellent oxygen permeability, low reagent permeability (low electrolyte permeability and low organic solvent permeability), and high-temperature tensile creep characteristics.

[0032] The identification of the types of functional groups and the determination of the number of functional groups mentioned above can be achieved using infrared spectroscopy.

[0033] Regarding the number of functional groups, specifically, it was determined using the following method. First, the above copolymer was cold-pressed to produce a film with a thickness of 0.25 mm to 0.3 mm. The film was analyzed by Fourier transform infrared spectroscopy to obtain the infrared absorption spectrum of the above copolymer, and a differential spectrum was obtained compared with the background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups in the above copolymer was calculated from the absorption peaks of specific functional groups shown in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.

[0034] N = I × K / t (A)

[0035] I: Absorbance

[0036] K: Correction coefficient

[0037] t: Membrane thickness (mm)

[0038] For reference, the absorption frequencies, molar absorptivity, and correction factors for some functional groups are shown in Table 1. Furthermore, the molar absorptivity was determined using FT-IR measurements of low-molecular-weight model compounds.

[0039] [Table 1]

[0040] Table 1

[0041]

[0042] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are tens of Kaiser (cm) lower than those of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. -1 ).

[0043] For example, the number of functional groups in -COF refers to the number of functional groups originating from the absorption frequency of -CF2COF, which is 1883 cm⁻¹. -1 The number of functional groups derived from the absorption peak at 1840 cm⁻¹ and the absorption frequency originating from -CH₂COF were also analyzed. -1 The total number of functional groups obtained from the absorption peak at the given location.

[0044] Functional groups are those present at the ends of the main chain or side chains of the copolymer, and those present in the main chain or side chains. The number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH.

[0045] The aforementioned functional groups are introduced into the copolymer, for example, through chain transfer agents or polymerization initiators used in the manufacturing of the copolymer. For instance, when an alcohol is used as a chain transfer agent, or when a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced to the ends of the copolymer's main chain. Alternatively, the aforementioned functional groups are introduced to the ends of the copolymer's side chains by polymerizing monomers containing functional groups.

[0046] By fluorinating the copolymer having such functional groups, copolymers having the number of functional groups within the aforementioned range can be obtained. That is, the copolymer of the present invention is preferably a fluorinated copolymer. The copolymer of the present invention also preferably has a -CF3 terminal group.

[0047] The melting point of the copolymer is preferably 285°C to 310°C, more preferably 290°C or higher, even more preferably 294°C or higher, and more preferably 303°C or lower. By keeping the melting point within the above range, a copolymer that provides superior mechanical strength, especially at high temperatures, can be obtained.

[0048] In this invention, the melting point can be determined using a differential scanning calorimeter (DSC).

[0049] The haze value of the copolymer of the present invention is preferably 12.0% or less, more preferably 11.5% or less. By keeping the haze value within the above range, when using the copolymer of the present invention to obtain molded bodies such as pipes, connectors, flow meter bodies, and bottles, it becomes easier to observe the interior of the molded body visually or with a camera, and it becomes easier to confirm the flow rate and balance of the contents. The haze value can be reduced by adjusting the content of PPVE units and the melt flow rate (MFR) of the copolymer. In the present invention, the haze value can be measured according to JIS K 7136.

[0050] The oxygen permeability coefficient of the copolymer is preferably 900 cm⁻¹. 3 ·mm / (m 2 The copolymer of the present invention exhibits excellent low oxygen permeability due to the appropriate adjustment of the PPVE unit content, melt flow rate (MFR), and number of functional groups in copolymers containing TFE and PPVE units. Therefore, oxygen does not easily permeate the molded body formed from the copolymer, and thus, for example, piping components and flow meter components obtained using the copolymer of the present invention can be suitably used for conveying reagents for which oxidation should be avoided.

[0051] In this invention, the oxygen permeability coefficient can be measured under test conditions of 70°C and 0% RH. The specific measurement of the oxygen permeability coefficient can be performed using the methods described in the examples.

[0052] The electrolyte permeability of the copolymer is preferably 6.6 g·cm / m. 2 The copolymers of the present invention exhibit excellent low electrolyte permeability due to the appropriate adjustment of the PPVE unit content, melt flow rate (MFR), and number of functional groups in copolymers containing TFE and PPVE units. That is, by using the copolymers of the present invention, it is possible to obtain molded articles that are difficult for reagents such as electrolytes to permeate.

[0053] In this invention, the electrolyte permeability can be measured at 60°C for 30 days. The specific measurement of electrolyte permeability can be performed using the methods described in the examples.

[0054] The preferred permeability of the copolymer methyl ethyl ketone (MEK) is 67.0 mg·cm / m. 2 • Less than 1 day. The copolymer of the present invention exhibits excellent MEK low permeability due to the appropriate adjustment of the PPVE unit content, melt flow rate (MFR), and number of functional groups in the copolymer containing TFE and PPVE units. That is, by using the copolymer of the present invention, it is possible to obtain a molded article that is not easily permeable by reagents such as MEK.

[0055] In this invention, MEK transmittance can be measured at 60°C for 60 days. The specific measurement of MEK transmittance can be performed using the method described in the examples.

[0056] The copolymers of the present invention can be manufactured by polymerization methods such as suspension polymerization, solution polymerization, emulsion polymerization, and bulk polymerization. Emulsion polymerization or suspension polymerization is preferred as the polymerization method. In these polymerizations, conditions such as temperature and pressure, polymerization initiators, and other additives can be appropriately set according to the composition and amount of the copolymer.

[0057] Oil-soluble or water-soluble free radical polymerization initiators can be used as polymerization initiators.

[0058] Oil-soluble free radical polymerization initiators can be well-known oil-soluble peroxides, and the following substances can be cited as representative examples:

[0059] Dialkyl percarbonate esters, such as di-n-propyl percarbonate, diisopropyl percarbonate, disec-butyl percarbonate, and di-2-ethoxyethyl percarbonate;

[0060] Peroxide esters such as tert-butyl peroxide isobutyrate and tert-butyl perpentyl peroxide;

[0061] Dialkyl peroxides such as di-tert-butyl peroxide;

[0062] Di[fluoro(or fluorochloro)acyl] peroxides; etc.

[0063] Examples of diacyl peroxides include those represented by [(RfCOO)-]2 (where Rf is a perfluoroalkyl, ω-hydroperfluoroalkyl, or fluorochloroalkyl).

[0064] Examples of di[fluoro(or fluorochloro)acyl]peroxides include, for example, di(ω-hydro-dodecanoyl)peroxide, di(ω-hydro-tetradecanoyl)fluoroheptanoyl)peroxide, di(ω-hydro-hexadecanoyl)fluorononanoyl)peroxide, di(perfluoropropionyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, and di... (ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecanoheptanyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecanoheptanyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecanoyl) peroxide, di(pentachlorotetrafluorodecanoyl) peroxide, di(undecachlorotetrafluorotetradecanoyl) peroxide, di(undecachlorotetrafluorotetradecanoyl) peroxide, etc.

[0065] Water-soluble free radical polymerization initiators can be well-known water-soluble peroxides, such as ammonium, potassium, and sodium salts of persulfate, perboric acid, perchloric acid, superphosphoric acid, and percarbonate; organic peroxides such as disuccinate peroxide and diglutaric acid peroxide; tert-butyl maleate peroxide; and tert-butyl hydroperoxide. Reducing agents such as sulfites can also be used in combination with peroxides, with the amount relative to the peroxide ranging from 0.1 to 20 times.

[0066] In polymerization, surfactants, chain transfer agents, and solvents can be used, and previously known substances can be used respectively.

[0067] As the surfactant, known surfactants can be used, such as nonionic surfactants, anionic surfactants, and cationic surfactants. Among these, fluorinated anionic surfactants are preferred, and more preferably, fluorinated anionic surfactants with straight or branched chains having 4 to 20 carbon atoms, with or without ether-bonded oxygen (i.e., oxygen atoms can be inserted between carbon atoms). The amount of surfactant added (relative to the polymerization water) is preferably 50 ppm to 5000 ppm.

[0068] Examples of chain transfer agents include: hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; thiols such as methyl mercaptan; and halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane. The amount of chain transfer agent added varies depending on the chain transfer constant of the compound used, and is typically used in the range of 0.01% to 20% by mass relative to the polymerization solvent.

[0069] Examples of solvents include water and mixed solvents of water and alcohol.

[0070] In suspension polymerization, fluorinated solvents can be used in addition to water. Examples of fluorinated solvents include hydrochlorofluorocarbons such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, and CF2ClCF2CFHCl; chlorofluorocarbons such as CF2ClCFClCF2CF3 and CF3CFClCFClCF3; hydrofluorocarbons such as CF3CFHCFHCF2CF2CF3, CF2HCF2CF2CF2CF2H, and CF3CF2CF2CF2CF2CF2CF2H; and CH3OC2F5, C Hydrofluoroethers such as H3OC3F5CF3CF2CH2OCHF2, CF3CHFCF2OCH3, CHF2CF2OCH2F, (CF3)2CHCF2OCH3, CF3CF2CH2OCH2CHF2, and CF3CHFCF2OCH2CF3; and perfluoroalkanes such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, and CF3CF2CF2CF2CF2CF3, with perfluoroalkanes being preferred. From the perspectives of suspension performance and economy, the amount of fluorinated solvent relative to the aqueous medium is preferably 10% to 100% by mass.

[0071] There is no particular limitation on the polymerization temperature, which can be 0 to 100°C. The polymerization pressure is appropriately determined according to the type, amount, vapor pressure, polymerization temperature, and other polymerization conditions used, and is usually 0 to 9.8 MPaG.

[0072] When an aqueous dispersion containing a copolymer is obtained through polymerization, the copolymer can be recovered by precipitating it, washing, and drying. Alternatively, when a copolymer is obtained as a slurry through polymerization, the copolymer can be recovered by removing the slurry from the reaction vessel, washing, and drying. The copolymer can also be recovered as a powder by drying.

[0073] The copolymer obtained through polymerization can also be granulated. There are no particular limitations on the granulation method; existing known methods can be used. For example, methods such as using a single-screw extruder, twin-screw extruder, or tandem extruder to melt-extrude the copolymer and cut it to a specified length to form granules can be employed. The extrusion temperature during melt extrusion needs to be varied depending on the melt viscosity of the copolymer and the manufacturing method; preferably, it is between the copolymer's melting point +20°C and the copolymer's melting point +140°C. There are no particular limitations on the copolymer cutting method; existing known methods such as wire cutting, thermal cutting, underwater cutting, and sheet cutting can be used. The volatile components in the granules can also be removed by heating (degassing treatment). Alternatively, the granules can be treated by contacting them with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.

[0074] The copolymer obtained by polymerization can also be fluorinated. Fluorination can be carried out by contacting the unfluorinated copolymer with a fluorinated compound. Through fluorination, thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, and -CONH2, as well as relatively thermally stable functional groups such as -CF2H, can be converted into extremely thermally stable -CF3. As a result, the total number of functional groups (-COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2, and -CF2H) of the copolymer can be easily adjusted to the above-mentioned range.

[0075] There are no particular limitations on fluorine-containing compounds; examples of fluorine radical sources that generate fluorine radicals under fluorination conditions can be cited. Examples of such fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3).

[0076] Fluorine radical sources such as F2 gas can be 100% concentrated, but from a safety perspective, it is preferable to mix them with an inert gas and dilute them to 5% to 50% by mass before use, and more preferably to 15% to 30% by mass. Examples of such inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.

[0077] The conditions for fluorination are not particularly limited; the molten copolymer can be brought into contact with a fluorinated compound. However, it is generally carried out at a temperature below the melting point of the copolymer, preferably between 20°C and 240°C, and more preferably between 100°C and 220°C. The fluorination treatment is typically carried out for 1 hour to 30 hours, preferably 5 hours to 25 hours. Fluorination is preferably carried out by bringing the unfluorinated copolymer into contact with fluorine gas (F2 gas).

[0078] The copolymers of the present invention can also be mixed with other components as needed to obtain compositions. Examples of other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, defluorinated hydrogen agents, etc.

[0079] Examples of fillers include silica, kaolin, clay, organoclay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium dioxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fiber. Examples of conductive agents include carbon black. Examples of plasticizers include dioctyl phthalate and pentaerythritol. Examples of processing aids include carnauba wax, sulfone compounds, low molecular weight polyethylene, and fluorinated additives. Examples of defluorinating agents include organonium and amidines.

[0080] Other polymers besides the copolymers described above can also be used as other components. Examples of other polymers include fluoropolymers, fluororubbers, and non-fluorinated polymers, in addition to the copolymers described above.

[0081] Examples of methods for manufacturing the above composition include: dry mixing of the copolymer with other components; pre-mixing of the copolymer with other components using a mixer, followed by melt mixing using a kneader, melt extruder, etc.; etc.

[0082] The copolymers of the present invention or the above-described compositions can be used as processing aids, molding materials, etc., and are preferably used as molding materials. Aqueous dispersions, solutions, suspensions, and copolymer / solvent systems of the copolymers of the present invention can also be used as coatings, or for encapsulation, impregnation, and film casting. However, the copolymers of the present invention have the above-described properties, and therefore are preferably used as the above-described molding materials.

[0083] The copolymer of the present invention or the above composition can also be molded to obtain a molded body.

[0084] The method for molding the above-mentioned copolymer or composition is not particularly limited, and examples include injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, and roll forming. Among these molding methods, extrusion molding, compression molding, injection molding, or transfer molding are preferred, and injection molding, extrusion molding, or transfer molding are more preferred because they can produce molded articles with high productivity. In other words, as the molded article, an extruded molded article, a compression molded article, an injection molded article, or a transfer molded article is preferred, and injection molded articles, extrusion molded articles, or transfer molded articles are more preferred because they can be produced with high productivity. Injection molded articles are even more preferred. By using injection molding to mold the copolymer of the present invention, injection molded articles with excellent surface smoothness can be obtained with high productivity.

[0085] The molded body containing the copolymer of the present invention can be, for example, a nut, bolt, joint, membrane, bottle, gasket, wire sheath, tube, hose, pipe, valve, sheet, seal, gasket, can, roller, container, stopcock, connector, filter housing, filter cover, flow meter, pump, wafer carrier, wafer box, etc.

[0086] The copolymers, compositions, or molded articles of the present invention can be used for, for example, the following purposes.

[0087] Food packaging films, lining materials for fluid transport pipelines used in food manufacturing processes, gaskets, sealing materials, thin sheets, and other fluid transport components for food manufacturing equipment;

[0088] Chemical stoppers, packaging films, lining materials for fluid delivery pipelines used in chemical manufacturing processes, gaskets, sealing materials, thin plates, and other reagent delivery components;

[0089] Inner lining components for reagent containers and piping in chemical equipment and semiconductor plants;

[0090] O-rings / pipes / gaskets, valve core materials, hoses, sealing materials, etc. used in the fuel system and peripheral devices of automobiles; hoses, sealing materials, and other fuel delivery components used in the AT system of automobiles.

[0091] The carburetor flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in the engine and peripheral devices of automobiles; brake hoses, air conditioning hoses, radiator hoses, wire sheathing materials, and other automobile components.

[0092] O-rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, washers, diaphragms, connectors and other reagent delivery components for semiconductor manufacturing equipment;

[0093] Coating and ink components for coating equipment, such as coating rollers, hoses, tubes, and ink containers;

[0094] Food and beverage conduits, hoses, belts, gaskets, connectors and other food and beverage conveying components, food packaging materials, and glass cooking equipment;

[0095] Pipes, hoses, and other components used for waste liquid transportation;

[0096] Pipes, hoses, and other components used for high-temperature liquid transfer;

[0097] Pipes, hoses and other steam piping components used in steam piping;

[0098] Corrosion-resistant tape for piping, such as tape wrapped around the piping on the deck of a ship;

[0099] Various coating materials, such as wire coating materials, optical fiber coating materials, transparent surface coating materials and backing agents applied to the light incident side of photovoltaic elements in solar cells;

[0100] The diaphragm and various sliding components such as gaskets in a diaphragm pump;

[0101] Weather-resistant covers for agricultural films, various roofing materials, and sidewalls;

[0102] Interior materials used in the construction industry, and glass-like covering materials such as non-combustible fire-resistant safety glass;

[0103] Lining materials such as laminated steel sheets used in the home appliance industry.

[0104] Further examples of fuel delivery components used in the fuel systems of the aforementioned automobiles include fuel hoses, filler hoses, and evaporator hoses. These fuel delivery components can also be used for fuels resistant to acidic gasoline, alcohol-based fuels, and fuels containing gasoline additives such as those resistant to methyl tert-butyl ether and amines.

[0105] The stoppers and packaging films used for the aforementioned chemicals exhibit excellent resistance to acids and other chemicals. Additionally, anti-corrosion tape wrapped around the piping of chemical equipment can also be cited as a component for transporting the aforementioned reagents.

[0106] Examples of such molded bodies include radiator water chambers for automobiles, reagent tanks, bellows, partitions, rollers, gasoline tanks, waste liquid conveying containers, high-temperature liquid conveying containers, and fish farming and aquaculture tanks.

[0107] Further examples of the molded bodies mentioned above include components used in automobile bumpers, door panels, dashboards, food processing devices, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, displays, LCD screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, prefabricated bathrooms, exhaust fans, lighting frames, etc.

[0108] Molded bodies containing the copolymers of the present invention exhibit low haze values, excellent abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics, and heat resistance to deformation after reagent impregnation. Therefore, they are suitable for use in nuts, bolts, joints, gaskets, valves, stopcocks, connectors, filter housings, filter covers, flow meters, pumps, etc. Filter housings containing the copolymers of the present invention have very low haze values, resulting in excellent internal visibility, for example, facilitating easy degassing operations. Furthermore, they are suitable for use as piping components (especially joints) in reagent delivery and as flow meter bodies that incorporate reagent flow paths in flow meters. The piping components and flow meter bodies of the present invention exhibit low haze values, excellent heat resistance to deformation after reagent impregnation, and excellent oxygen permeability, low reagent permeability, abrasion resistance at 150°C, high-temperature tensile creep characteristics, and high-temperature rigidity. Therefore, the piping components and flowmeter body of the present invention have excellent internal visibility, especially in the flowmeter body, where the internal float can be easily observed visually or with a camera, and it is also suitable for flow measurement of high-temperature reagents. Furthermore, the piping components and flowmeter body of the present invention can be manufactured at extremely high injection speeds even with thin-walled portions, resulting in an aesthetically pleasing appearance.

[0109] Molded articles containing the copolymers of the present invention can be manufactured by injection molding at extremely high injection speeds. They exhibit excellent abrasion resistance at 150°C, low oxygen permeability, low reagent permeability, high-temperature rigidity, high-temperature tensile creep characteristics, and heat deformation resistance after reagent impregnation. Therefore, they are suitable for use as gaskets, seals, and other compressed components. The gaskets or seals of the present invention can be manufactured at low cost by injection molding. They are not easily deformed even when placed in areas subject to frequent opening and closing. They also exhibit excellent abrasion resistance at 150°C, high-temperature tensile creep characteristics, low oxygen permeability, low reagent permeability, and crack resistance to high-temperature reagents. The compressed components of the present invention exhibit excellent low oxygen permeability, making them suitable for use as piping components for conveying reagents that should be protected from oxidation.

[0110] The size and shape of the compressed member of the present invention can be appropriately set according to the application and are not particularly limited. The shape of the compressed member of the present invention can be, for example, ring-shaped. In addition, the compressed member of the present invention can have a circular, elliptical, or quadrilateral shape with rounded corners when viewed from above, and has a through hole in its central part.

[0111] The compressed member of the present invention is preferably used as a component for constructing a non-aqueous electrolyte battery. Due to its excellent low electrolyte permeability, the compressed member of the present invention is particularly suitable as a component used in contact with the non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed member of the present invention can have a liquid-contacting surface for contacting the non-aqueous electrolyte in a non-aqueous electrolyte battery.

[0112] As for non-aqueous electrolyte batteries, there are no particular limitations as long as the battery contains a non-aqueous electrolyte; examples include lithium-ion secondary batteries and lithium-ion capacitors. Furthermore, components constituting non-aqueous electrolyte batteries include sealing components and insulating components.

[0113] The non-aqueous electrolyte is not particularly limited and can be one or more of the following known solvents: propylene carbonate, ethylene carbonate, butyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The non-aqueous electrolyte battery may further include an electrolyte. The electrolyte is not particularly limited and can be LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.

[0114] The compressed component of the present invention can preferably be used as a sealing component such as a sealing gasket or sealing pad, or as an insulating component such as an insulating gasket or insulating sealing pad. A sealing component is used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating component is used for electrical insulation. The compressed component of the present invention can also be used for both sealing and insulation purposes.

[0115] The compressed member of the present invention, due to containing the aforementioned copolymer, possesses excellent insulating properties. Therefore, when the compressed member of the present invention is used as an insulating member, it can be firmly and tightly bonded to two or more conductive members, preventing short circuits for a long period of time.

[0116] By using extrusion molding to form the copolymer of the present invention, even with a small core diameter, the coating will not break. A thin coating layer can be formed on a small-diameter core at a high traction speed, and a coating layer with excellent electrical properties can be formed. Therefore, the copolymer of the present invention is suitable for use as a material for forming wire coatings. Thus, coated wires having a coating layer containing the copolymer of the present invention exhibit almost no defects such as sparking, even with a small core diameter and a thin coating layer, and also possess excellent electrical properties.

[0117] The coated wire has a core wire and a coating layer disposed around the core wire containing the copolymer of the present invention. For example, an extruded body formed by melt-extruding the copolymer of the present invention onto the core wire can be used as the coating layer. The coated wire is suitable for LAN cables (Eathernet cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is particularly suitable for transmission cables such as LAN cables (Eathernet cables) and high-frequency transmission cables.

[0118] For example, copper, aluminum, or other metallic conductors can be used as the core wire material. The core wire diameter is preferably 0.02 mm to 3 mm. More preferably, the core wire diameter is 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. Even more preferably, the core wire diameter is 2 mm or less.

[0119] Specific examples of core wires include AWG (American wire gauge)-46 (solid copper wire with a diameter of 40μm), AWG-26 (solid copper wire with a diameter of 404μm), AWG-24 (solid copper wire with a diameter of 510μm), and AWG-22 (solid copper wire with a diameter of 635μm).

[0120] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm. The thickness of the coating layer is also preferably less than 2.0 mm.

[0121] Coaxial cables are an example of high-frequency transmission cables. Coaxial cables typically have a structure consisting of an inner conductor, an insulating sheath, an outer conductor layer, and a protective sheath layer layered sequentially from the core to the outer periphery. Molded bodies containing the copolymer of the present invention can be suitable as the insulating sheath layer containing the copolymer. The thickness of each layer in the above structure is not particularly limited; typically, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating sheath is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective sheath is about 0.5 mm to 2 mm.

[0122] The coating may contain air bubbles, which are preferably evenly distributed in the coating.

[0123] The average bubble diameter is not limited, but is preferably 60 μm or less, more preferably 45 μm or less, further preferably 35 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and especially preferably 23 μm or less. Furthermore, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by acquiring an electron microscope image of the wire cross-section, calculating the diameter of each bubble using image processing, and then averaging the results.

[0124] The foaming rate of the coating layer can be 20% or more. More preferably, it is 30% or more, further preferably 33% or more, and even more preferably 35% or more. There is no particular upper limit, for example, 80%. The upper limit of the foaming rate can also be 60%. The foaming rate is calculated as ((specific gravity of wire coating material - specific gravity of coating layer) / specific gravity of wire coating material) × 100. The foaming rate can be adjusted appropriately according to the application, for example, by adjusting the gas insertion amount in the extruder described later, or by selecting the type of dissolved gas.

[0125] The coated wire may also have other layers between the core wire and the coating layer, and may further have other layers (outer layers) around the coating layer. If the coating layer contains air bubbles, the wire of the present invention may also be a two-layer structure (skin-foam body) with a non-foamed layer inserted between the core wire and the coating layer; a two-layer structure (foam body-skin body) with a non-foamed layer coated on the outer layer; and a three-layer structure (skin-foam body-skin body) with a non-foamed layer coated on the outer layer of the skin-foam body. The non-foamed layer is not particularly limited and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], and resins such as polyvinyl chloride [PVC].

[0126] Coated wires can be manufactured, for example, by heating a copolymer using an extruder and extruding it onto the core wire while the copolymer is in a molten state to form a coating.

[0127] During the formation of the coating layer, the copolymer can also be heated, and gas can be introduced into the copolymer while it is in a molten state to form the aforementioned coating layer containing bubbles. The gas can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture of these gases. The gas can be introduced into the heated copolymer in the form of pressurized gas, or it can be generated by mixing a chemical foaming agent into the copolymer. The gas dissolves in the molten copolymer.

[0128] In addition, the copolymers of the present invention are suitable for use as materials in products for high-frequency signal transmission.

[0129] As for the aforementioned high-frequency signal transmission products, there are no particular limitations as long as the product is used for high-frequency signal transmission. Examples include (1) insulating boards for high-frequency circuits, insulating materials for connecting components, printed wiring boards, and other molded boards; (2) bases for high-frequency vacuum tubes, radomes, and other molded bodies; and (3) sheathed wires such as coaxial cables and LAN cables. The aforementioned high-frequency signal transmission products are suitable for use in satellite communication equipment, mobile phone base stations, and other equipment that utilizes microwaves, especially microwaves from 3 GHz to 30 GHz.

[0130] In the aforementioned high-frequency signal transmission products, the copolymer of the present invention, from the perspective of low dielectric loss tangent, is suitable for use as an insulator.

[0131] As for the molded plate described in (1) above, a printed wiring substrate is preferred from the perspective of obtaining good electrical characteristics. There are no particular limitations on the printed wiring substrate described above; examples include printed wiring substrates for electronic circuits in mobile phones, various computers, and communication devices. As for the molded body described in (2) above, an antenna radome is preferred from the perspective of low dielectric loss.

[0132] The embodiments have been described above, but it is understood that various changes can be made to the methods and details without departing from the spirit and scope of the claims.

[0133] Example

[0134] Next, embodiments will be given to illustrate the implementation of the present invention, but the present invention is not limited to the embodiments described.

[0135] The values ​​in the examples were measured using the following methods.

[0136] (Monomer content)

[0137] The content of each monomer unit was determined by an NMR analyzer (e.g., an AVANCE300 high-temperature probe manufactured by Bruker BioSpin).

[0138] (Mel flow rate (MFR))

[0139] According to ASTM D1238, the mass (g / 10 min) of polymer flowing out of a nozzle with an inner diameter of 2.1 mm and a length of 8 mm per 10 minutes was determined using a melt indexer G-01 (manufactured by Toyo Seiki Co., Ltd.) at 372°C and a load of 5 kg.

[0140] (Number of functional groups)

[0141] The copolymer granules were cold-pressed to produce films with a thickness of 0.25 mm to 0.3 mm. The films were then scanned 40 times using a Fourier transform infrared spectroscopy (FT-IR) device (Spectrum One, PerkinElmer) to obtain infrared absorption spectra. A differential spectrum was obtained between this spectrum and the background spectrum of the fully fluorinated film, which lacks functional groups. The concentration of the sample relative to each 1 × 10⁻⁶ functional group was calculated from the absorption peaks of specific functional groups observed in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.

[0142] N = I × K / t (A)

[0143] I: Absorbance

[0144] K: Correction coefficient

[0145] t: Membrane thickness (mm)

[0146] For reference, the absorption frequencies, molar absorptivity, and correction factors for the functional groups in this invention are shown in Table 2. The molar absorptivity was determined by FT-IR measurements of the low-molecular-weight model compounds.

[0147] [Table 2]

[0148] Table 2

[0149]

[0150] (Melting point)

[0151] The first heating was performed using a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science) at a heating rate of 10°C / min, from 200°C to 350°C. Then, the temperature was cooled from 350°C to 200°C at a cooling rate of 10°C / min. The second heating was performed again at a heating rate of 10°C / min, from 200°C to 350°C. The melting point was determined from the peak value of the melting curve generated during the second heating process.

[0152] Comparative Example 1

[0153] 51.8 L of pure water was added to a 174 L autoclave, and after thorough nitrogen purging, 40.9 kg of perfluorocyclobutane, 2.56 kg of perfluoropropyl vinyl ether (PPVE), and 2.29 kg of methanol were added. The system temperature was maintained at 35 °C, and the stirring speed was maintained at 200 rpm. Next, tetrafluoroethylene (TFE) was injected to 0.64 MPa, followed by the addition of 0.103 kg of a 50% methanol solution of di-n-propyl peroxide dicarbonate, to initiate polymerization. Since the pressure within the system decreased as polymerization progressed, TFE was continuously supplied to maintain a constant pressure, with an additional 0.055 kg of PPVE added for every 1 kg of TFE supplied. Polymerization was terminated when the additional TFE supply reached 40.9 kg. Unreacted TFE was released, and the autoclave pressure was restored to atmospheric pressure. The resulting reaction product was then washed with water and dried to obtain 43.1 kg of powder.

[0154] The obtained powder was melt-extruded at 360°C using a screw extruder (trade name: PCM46, manufactured by Ikebe Co., Ltd.) to obtain TFE / PPVE copolymer granules. The PPVE content of the obtained granules was determined using the method described above.

[0155] The obtained granules were placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.) and heated to 210°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, the reactor was temporarily evacuated, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another evacuation and introduction of F2 gas. This process of introducing F2 gas and evacuating the reactor was repeated once every hour, and the reaction was carried out at 210°C for 10 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction. Various physical properties of the fluorinated granules were measured using the above method.

[0156] Comparative Example 2

[0157] The amount of PPVE was changed to 2.75 kg, the amount of methanol was changed to 3.02 kg, the amount of PPVE was changed to 0.058 kg added for every 1 kg of TFE supplied, the heating temperature of the vacuum vibrating reactor was changed to 170°C, and the reaction was changed to be carried out at 170°C for 5 hours, resulting in 43.3 kg of dry powder. Otherwise, fluorinated granules were obtained in the same manner as in Comparative Example 1.

[0158] Comparative Example 3

[0159] The amount of PPVE was changed to 3.86 kg, the amount of methanol was changed to 2.49 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, and the amount of PPVE was changed to 0.078 kg added for every 1 kg of TFE supplied, resulting in 44.1 kg of dry powder. Otherwise, fluorinated granules were obtained in the same manner as in Comparative Example 1.

[0160] Comparative Example 4

[0161] The amount of PPVE was changed to 3.66 kg, the amount of methanol was changed to 4.78 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, and the amount of PPVE was changed to 0.074 kg added for every 1 kg of TFE supplied, resulting in 43.9 kg of dry powder. Otherwise, unfluorinated granules were obtained in the same manner as in Comparative Example 1.

[0162] Comparative Example 5

[0163] The amount of PPVE was changed to 3.13 kg, the amount of methanol was changed to 1.80 kg, and the amount of PPVE was changed to an additional 0.065 kg for every 1 kg of TFE supplied, resulting in 43.6 kg of dry powder. Otherwise, fluorinated granules were obtained in the same manner as in Comparative Example 1.

[0164] Example 1

[0165] The amount of PPVE was changed to 2.94 kg, the amount of methanol was changed to 4.91 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, and the amount of PPVE was changed to 0.062 kg added for every 1 kg of TFE supplied, resulting in 43.4 kg of dry powder. Otherwise, fluorinated granules were obtained in the same manner as in Comparative Example 1.

[0166] Example 2

[0167] The amount of PPVE was changed to 3.21 kg, the amount of methanol was changed to 4.46 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, and the amount of PPVE was changed to 0.066 kg added for every 1 kg of TFE supplied, resulting in 43.6 kg of dry powder. Otherwise, fluorinated granules were obtained in the same manner as in Comparative Example 1.

[0168] Example 3

[0169] The amount of PPVE was changed to 3.47 kg, the amount of methanol was changed to 4.30 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, and the amount of PPVE was changed to 0.071 kg added for every 1 kg of TFE supplied, resulting in 43.8 kg of dry powder. Otherwise, fluorinated granules were obtained in the same manner as in Comparative Example 1.

[0170] Example 4

[0171] The amount of PPVE was changed to 3.73 kg, the amount of methanol was changed to 4.32 kg, the amount of 50% methanol solution of di-n-propyl peroxide was changed to 0.051 kg, the amount of PPVE was changed to 0.075 kg added for every 1 kg of TFE supplied, the heating temperature of the vacuum vibrating reactor was changed to 180°C, and the reaction was changed to be carried out at 180°C for 10 hours, resulting in 44.0 kg of dry powder. Otherwise, fluorinated granules were obtained in the same manner as in Comparative Example 1.

[0172] Using the granules obtained in the examples and comparative examples, various physical properties were determined by the methods described above. The results are shown in Table 3.

[0173] [Table 3]

[0174] Table 3

[0175]

[0176] The “<6” in Table 3 refers to the number of functional groups being less than 6.

[0177] Next, the obtained granules were used to evaluate the following properties. The results are shown in Table 4.

[0178] (Haze value)

[0179] Using granulation and a hot press molding machine, sheets with a thickness of approximately 1.0 mm were produced. Using a haze meter (trade name: NDH7000SP, manufactured by Nippon Denshoku Kogyo Co., Ltd.), the sheets were immersed in a quartz cell containing pure water according to JIS K 7136, and the haze value was measured.

[0180] (Abrasion test)

[0181] Using a granulation and hot-press molding machine, sheet-like test pieces with a thickness of approximately 0.2 mm were prepared, from which 10 cm × 10 cm test pieces were cut. The prepared test pieces were fixed on the test bench of a Tiber abrasion testing machine (No. 101 Special Type Tiber Abrasion Testing Machine, manufactured by Yasuda Seiki Co., Ltd.). Abrasion tests were conducted using the Tiber abrasion testing machine under the following conditions: test piece surface temperature 150°C, load 500 g, abrasion wheel CS-10 (ground with #240 abrasive paper for 20 revolutions), and rotation speed 60 rpm. The weight of the test piece was measured after 1000 revolutions, and the same test piece was further tested after 5000 revolutions, and the weight was measured again. The abrasion amount was calculated using the following formula.

[0182] Wear amount (mg) = M1 - M2

[0183] M1: Weight of the test piece after 1000 revolutions (mg)

[0184] M2: Weight of the test piece (mg) after 5000 revolutions.

[0185] (Oxygen permeability coefficient)

[0186] Using granulation and a hot press molding machine, sheet-like test pieces with a thickness of approximately 0.1 mm were prepared. Using the obtained test pieces, the oxygen permeability was measured using a differential pressure gas permeability meter (L100-5000 type gas permeability meter, manufactured by Systech Illinois) according to the method described in JIS K7126-1:2006. The resulting permeability area was 50.24 cm². 2 The oxygen permeability was measured at a test temperature of 70℃ and a test humidity of 0%RH. Using the obtained oxygen permeability and the thickness of the test piece, the oxygen permeability coefficient was calculated using the following formula.

[0187] Oxygen permeability (cm) 3 ·mm / (m 2 ·24h·atm))=GTR×d

[0188] GTR: Oxygen permeability (cm) 3 / (m 2 ·24h·atm))

[0189] d: Thickness of the test piece (mm)

[0190] (Electrolyte permeability)

[0191] Using granulation and a thermoforming machine, sheet-like test pieces with a thickness of approximately 0.2 mm were produced. These were then placed in a test cup (with a transparency area of ​​12.56 cm²). 2 Add 10g of dimethyl carbonate (DMC) to the container, cover it with a sheet test piece, and secure it tightly with a PTFE gasket. Ensure the sheet test piece is in contact with the DMC, maintain the temperature at 60℃ for 30 days, then remove it and allow it to stand at room temperature for 1 hour to measure the mass loss. Calculate the DMC transmittance (g·cm / m) using the following formula. 2 ).

[0192] Electrolyte permeability (g·cm / m) 2 = Mass reduction (g) × Thickness of sheet test piece (cm) / Transmitting area (m²) 2 )

[0193] (Methyl ethyl ketone (MEK) transmittance)

[0194] Using granulation and a thermoforming machine, sheet-like test pieces with a thickness of approximately 0.1 mm were produced. These were then placed in a test cup (with a transparency area of ​​12.56 cm²). 2 Add 10g of MEK to the container, cover it with a test sheet, and secure it tightly with a PTFE gasket. Ensure the test sheet is in contact with the MEK. After maintaining this temperature at 60℃ for 60 days, remove the container and allow it to stand at room temperature for 1 hour to measure the mass loss. Calculate the MEK transmittance (mg·cm / m²) using the following formula. 2 ·sky).

[0195] MEK transmittance (mg·cm / m) 2 • Days) = [Mass reduction (mg) × Thickness of the test piece (cm)] / [Transmitting area (m²)] 2 )·Number of days (days)]

[0196] (Deflection under load at 95℃)

[0197] Using granulation and a hot press molding machine, sheet-like test pieces with a thickness of approximately 3 mm were prepared. 80 × 10 mm test pieces were cut from these pieces and heated in an electric furnace at 100°C for 20 hours. In addition to using the obtained test pieces, tests were conducted according to the method described in JIS K-K7191-1 using a heat distortion tester (manufactured by Yasuda Seiki Co., Ltd.) under the conditions of a test temperature of 30°C to 150°C, a heating rate of 120°C / hour, a bending stress of 1.8 MPa, and the flatwise method. The load deflection was calculated using the following formula. Sheets with low load deflection at 95°C exhibit excellent high-temperature rigidity.

[0198] Load-induced deflection (%) = a2 / a1 × 100

[0199] a1: Thickness of the test piece before the test (mm)

[0200] a2: Deflection at 95℃ (mm)

[0201] (Tensile creep test)

[0202] Tensile creep strain was determined using a Hitachi High-Tech TMA-7100. Sheets approximately 0.1 mm thick were prepared using a granulator and thermoforming machine. Samples 2 mm wide and 22 mm long were then fabricated from these sheets. The samples were mounted in the measuring fixture with a 10 mm gap between the clamps. A cross-sectional load of 2.41 N / mm² was applied to the samples. 2 The sample was subjected to a load at 240°C, and the displacement (mm) of its length was measured from 90 minutes to 300 minutes after the start of the test. The ratio of the displacement (mm) to the initial sample length (10mm) was calculated (tensile creep strain (%)). Samples with low tensile creep strain (%) measured at 240°C for 300 minutes do not easily elongate even under tensile loads in very high-temperature environments, demonstrating excellent high-temperature tensile creep characteristics.

[0203] (Reagent impregnation crack test (heat resistance deformation after reagent impregnation))

[0204] Sheets approximately 2 mm thick were produced using granulation and a thermoforming machine. The resulting sheets were punched using a 13.5 mm × 38 mm rectangular dumbbell to obtain three test pieces. A 19 mm × 0.45 mm notch was cut at the center of the long side of each test piece according to ASTM D1693. The three notched test pieces and 25 g of 3% (w / w) hydrogen peroxide aqueous solution were placed in a 100 mL polypropylene bottle and heated at 100°C for 20 hours. The notched test pieces were then removed. The three notched test pieces were mounted in a stress cracking test fixture according to ASTM D1693 and heated at 150°C for 24 hours. The notches and their surrounding areas were visually observed, and the number of cracks was counted. Sheets that did not crack exhibited excellent heat resistance even after immersion in the reagent.

[0205] ○: The number of cracks is 0

[0206] ×: The number of cracks is more than 1.

[0207] (Surface smoothness)

[0208] The copolymer was injection molded using an injection molding machine (Sumitomo Heavy Industries, Ltd., SE50EV-A) with a barrel temperature of 390°C, a mold temperature of 190°C, and an injection speed of 130 mm / s. A 4-cavity mold (15 mm × 15 mm × 0.6 mm) with Cr plating on HPM38 was used as the mold. The surface of the resulting injection-molded body was visually inspected, and the surface smoothness was evaluated according to the following criteria.

[0209] Advantages: Smooth surface.

[0210] Good: No more than 1 / 4 roughnesses are observed on the surface only in the part near the gate of the mold.

[0211] It is permissible to observe more than 2 or 4 roughnesses only on the surface of the portion located near the gate of the mold.

[0212] Poor: Roughness is observed in most parts of the surface.

[0213] (Wire sheathing characteristics)

[0214] use The wire coating forming machine (manufactured by Tanabe Plastic Machinery Co., Ltd.) extrudes coating granules onto a silver-plated conductor of 19 stranded wires with a thickness of 0.05mm to obtain coated wires.

[0215] The extrusion molding conditions for wire coating are as follows.

[0216] a) Core conductor: The conductor diameter is approximately 0.25mm (0.05mm × 19 strands).

[0217] b) Coating thickness: 0.20mm

[0218] c) Diameter of the covered wire: 0.65mm

[0219] d) Wire pulling speed: 250m / minute

[0220] e) Extrusion conditions:

[0221] • Single-screw extrusion molding machine with a barrel shaft diameter of 30mm and an L / D ratio of 24

[0222] • Mold (inner diameter) / sheet (outer diameter) = 9.2mm / 4.0mm

[0223] Extruder set temperatures: Barrel section C-1 (330℃), Barrel section C-2 (360℃), Barrel section C-3 (375℃), Head H (390℃), Die head D-1 (405℃), Die head D-2 (395℃). Core wire preheating is set to 80℃.

[0224] (2-1) Whether the covering is broken

[0225] Continuous wire coating molding is performed. If the coating breaks more than once within 1 hour, it is considered as non-continuous molding (×), and if the coating does not break, it is considered as continuous molding (○).

[0226] (2-2) Number of sparks

[0227] A DENSOK HIGH FREQ SPARK TESTER is installed online on the wire sheath to evaluate for any defects in the wire sheath at 1500V. The process is repeated for 1 hour; zero sparks are considered acceptable (○), while the presence of sparks is considered unacceptable (×).

[0228] (2-3) Outer diameter movement range

[0229] The outer diameter was continuously measured for 1 hour using an outer diameter measuring instrument (Zumbach ODAC18XY). The outer diameter was 0.65 mm relative to the target outer diameter. For the maximum and minimum values, the measured values ​​were rounded to the third decimal place. The case of ±0.01 mm was recorded as ±0.01, the case of ±0.02 mm was recorded as ±0.02, the case of ±0.03 mm was recorded as ±0.03, and the case of a broken cover was recorded as ×.

[0230] (Dielectric loss tangent)

[0231] The granules were melt-molded to produce cylindrical test pieces with a diameter of 2 mm. These test pieces were then placed on a 6 GHz cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd., and measurements were taken using a network analyzer manufactured by Agilent Technologies. The measurement results were analyzed using the analysis software "CPMA" manufactured by Kanto Electronics Application Development Co., Ltd. on a personal computer connected to the network analyzer, thereby determining the dielectric loss tangent (tanδ) at 20°C and 6 GHz.

[0232]

Claims

1. A copolymer comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, The content of perfluoro(propyl vinyl ether) units is 2.14 mol% to 3.00 mol% relative to all monomer units. The content of tetrafluoroethylene units relative to all monomer units is 97.00 mol% to 97.86 mol%. The melt flow rate, measured as the mass of polymer flowing out every 10 minutes from a nozzle with an inner diameter of 2.1 mm and a length of 8 mm at 372°C and a load of 5 kg, was 33.0 g / 10 min to 50.0 g / 10 min, where the mass of the polymer is expressed in g / 10 min. The number of functional groups -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, and -CH2OH relative to 10 6 The number of carbon atoms in the main chain is less than 50.

2. An injection-molded article comprising the copolymer of claim 1.

3. A coated wire having a coating layer comprising the copolymer of claim 1.

4. A molded article comprising the copolymer of claim 1, wherein, The molded body is a connector, a flow meter body, or a wire cover.

Citation Information

Patent Citations

  • usb cable for ultra high speed data transmission

    JP2018523272A

  • Tetrafluoroethylene / hexafluoropropylene copolymer, and electric wire

    CN105980426A

  • Tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer and preparation method thereof

    CN110790854A